Interrupted time series analysis to evaluate the impact of COVID-19-pandemic on the incidence of notifiable infectious diseases in the Lazio region, Italy - Martina Spaziante; Sara Leone; Maurizio D’Amato; Gabriella De Carli; Gilda Tonziello; Giorgio Nicolò Malatesta; Alessandro Agresta; Claudia De Santis; Valentina Vantaggio; Giovanni Pitti; Maria Concetta Fusco; Pierluca Piselli; et al. (BMC Public Health)
Abstract Background The coronavirus disease 2019 (COVID-19) emergency has represented a profound upheaval in the dynamics of infectious diseases transmission worldwide. This phenomenon has been at least in part driven by the introduction of non-pharmaceutical interventions (NPIs), implemented to counteract viral transmission. Our study aimed to assess the magnitude and the features of the impact of the COVID-19 pandemic on the incidence of notifiable infectious diseases (NIDs) in the Lazio region, Italy. Methods Data on NIDs in the Lazio Region with symptom onset date included in the time interval from 1 January 2017 to 31 December 2023 were collected from different surveillance system databases available at SERESMI/Lazio Region Unit and classified into five categories based on the main transmission route of the disease. Descriptive statistics were performed and interrupted time series (ITS) analysis was used to assess the effect of the COVID-19 pandemic and subsequent recovery period on monthly NIDs cases. Results Immediately after the start of the COVID-19 pandemic, a significant, sharp and immediate reduction in monthly cases was recorded for all NIDs (-86.73%), regardless of the transmission route. The decrease was particularly significant for vector-borne, food-borne and respiratory-transmitted diseases (RDs), and in general in females. During the COVID-19 recovery phase, monthly cases of all NIDs showed a significant positive level change, particularly significant for sexually transmitted/blood-borne diseases, contact diseases and RDs. Discussion The COVID-19 pandemic has been responsible for the disruption of all NIDs transmission patterns, while the magnitude and dynamics of its effects varied depending on the transmission route; furthermore, the impact of the pandemic wave was still noticeable during the post-COVID-19 era and the incidence trajectories of NIDs in this phase were peculiar for each disease category.